Strategi Asesmen Kebutuhan Siswa di Sekolah Menengah Pertama: Perancangan Berbasis Data dan Analitik - Habsy, Bakhrudin All; Azizah, Erliyana Freida Nur; Sofiana, Sofiana (TSAQOFAH, 2024)
This study aims to design a data-driven and analytical-based strategy for assessing student needs in Junior High School (JHS). A qualitative approach was employed, utilizing observation and literature review methods. The study population consisted of JHS students, with samples randomly selected from various schools. Research instruments included social media observation and literature review. Instrument validity and reliability were ensured through literature comparison. Data were analyzed through data reduction and triangulation approaches. The results indicate that JHS student needs assessment aims to measure learning achievement, provide feedback, promote active learning, adapt teaching methods, assess program effectiveness, and identify special needs. Assessment principles, types, data-driven design, and needs analytics are the main focuses. The implications of this research are to enhance the quality of education in JHS through more responsive and effective assessments. Suggestions for further research include involving more educational stakeholders to ensure program relevance and responsiveness. This study contributes to the development of better education in Indonesia.